Hubungan Antara Motivasi Belajar dan Pemahaman Matematika Dalam Kurikulum Merdeka Belajar Pada siswa kelas IV SDN 01 Bengkayang - Musta, Paskarian; Yosua Damas Sadewo (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aimed to determine the relationship between learning motivation and mathematical understanding in the Merdeka Curriculum among fourth-grade students at SDN 01 Bengkayang. This research employed a quantitative approach with a correlational method. The population and sample consisted of 30 fourth-grade students. Data were collected using a learning motivation questionnaire and a mathematics understanding test. The instruments had been tested for validity and reliability. Data analysis was conducted using descriptive statistics, normality test, linearity test, Spearman Rank correlation test, and coefficient of determination with the assistance of IBM SPSS Statistics. The results showed that the average score of students' learning motivation was 77.23 and categorized as good, while the average score of mathematical understanding was 77.33 and categorized as good. The Spearman Rank correlation test yielded a correlation coefficient (ρ) of 0.242 with a significance value of 0.197. Since the significance value was greater than 0.05, there was no significant relationship between learning motivation and mathematical understanding. The coefficient of determination showed that learning motivation contributed 5.86% to students' mathematical understanding, while 94.14% was influenced by other factors. Therefore, learning motivation had a low positive but insignificant relationship with mathematical understanding among fourth-grade students at SDN 01 Bengkayang.